A wideband signal conditioning system for high voltage measurements using a transconductance topology - Agjee, F. M. D. E. (Faatima, Moosa, Dawood, Ebrahim) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--Stellenbosch University, 2000.